2020
DOI: 10.3389/fpsyt.2020.00423
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Interpersonal and Affective Risk Factors for Pathological Gaming

Abstract: Internet gaming is among the most popular entertainment options, worldwide; however, a considerable proportion of gamers show symptoms of pathological gaming. Internet gaming disorder (IGD) has been proposed to describe a behavioral addiction, which shares many similarities, both physical and psychological, with substance use disorder. Environmental factors, such as interpersonal and relationship dynamics during childhood and adolescence, have been suggested to modulate the onset and trajectories of IGD. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 79 publications
(100 reference statements)
3
15
0
2
Order By: Relevance
“…What is unique about the present study is that this relationship also extends to gaming disorder. This not only replicates previous studies reporting positive relationships between bullying victimization and PVG [ 52 , 53 , 54 ], yet provides evidence for the role of mental health symptoms in this relationship, accounting for 16.1% of the variance in PVG severity. The extent of the variance explained in this model points to the fact that various factors other than bullying victimization, externalizing and internalizing problems may explain youth PVG, including self-esteem, impulsivity, attention difficulties, social competencies and parental relationship quality [ 16 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…What is unique about the present study is that this relationship also extends to gaming disorder. This not only replicates previous studies reporting positive relationships between bullying victimization and PVG [ 52 , 53 , 54 ], yet provides evidence for the role of mental health symptoms in this relationship, accounting for 16.1% of the variance in PVG severity. The extent of the variance explained in this model points to the fact that various factors other than bullying victimization, externalizing and internalizing problems may explain youth PVG, including self-esteem, impulsivity, attention difficulties, social competencies and parental relationship quality [ 16 ].…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, some studies have found that frequent video game playing has been associated with increases in cyberbullying perpetration (or of being both a victim and perpetrator of bullying [i.e., bully-victims]), within and outside online gaming environments [ 43 , 44 , 45 , 48 , 49 , 50 , 51 ]. Specific to PVG, direct positive relationships have been identified between bullying victimization and PVG [ 52 , 53 , 54 ]. However, little research has investigated the potential mediators explaining the relationship between these variables.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, subjects reporting PUI may be more vulnerable to stressful events or more prone to develop PTSD. Given that a causal link cannot be obtained by our results, previous studies, in accordance with the former hypothesis, showed an association between childhood trauma experience and PUI, highlighting the possible role of PUI as a maladaptive coping method to traumatic events and distressful memories ( 40 , 43 ).…”
Section: Discussionsupporting
confidence: 72%
“…This is a particularly promising research pathway, as suggested by the results of the few studies that have been focusing on PUI in PTSD ( 44 ). Literature, in fact, showed a relationship between a history of stressful events or sexual abuse and PUI among adolescents and young adults ( 40 43 ) and an increased risk of PTSD development among adolescents with PUI ( 25 ). While research on this issue is to date at its preliminary stage, the association between PTSD and other addiction disorders such as substance or alcohol use disorder and gambling disorder, are widely acknowledged ( 32 , 51 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies report the symptom severity of GD to be associated with increased perceived stress [78][79][80][81][82][83] and emotional trauma or maltreatment during childhood [84,85]. Furthermore, Canale et al [79] could show that stress was positively correlated with hours of game play per week.…”
Section: Neuroscientific and Psychological Findings On Stress In Gdmentioning
confidence: 99%